Prevalence and risk factors of acid peptic ulcer disease at a tertiary care hospital - Chavan, Manohar Shankarrao; Bhaktavatsalam, M. (International Journal of Advances in Medicine, 2018)
Background: In day to day practice, at outpatient department of General Medicine, at Mahavir Institute of Medical Sciences, Vikarabad, Telangana, India authors are coming across a significant number of patients with acid peptic disease (APD). This prompted us to carry out the present study. The objective is to study the prevalence, risk factors of acid peptic disease and to give suitable recommendations Methods: Present study was hospital based cross sectional study carried out at outpatient department of General Medicine for a period of ten months from June 2017 to March 2018 among 307 outpatients. Results: The prevalence of acid peptic disease was found to be very high in the present study i.e. 38.1%. This was very high compared to the available literature. The prevalence of acid peptic disease was significantly associated with increasing age, lower social class, alcohol use, tea use and NSAID use. Acid peptic disease was not found to be associated with sex, residence, literacy, smoking, coffee intake, and obesity. Conclusions: Prevalence of acid peptic disease was found to be very high in the present study. Hence there is a need to institute the preventive and control measures to bring down the prevalence. At the same time the people in the surroundings should be made aware of this health problems and its risk factors.